Descartes and Kant: Two opposing positions on Anselm's Ontological Argument - Martín Cieri (Perspectivas Metodológicas​)
This work tries to go through two different positions regarding Anselmo's ontological argument: the Cartesian and the Kantian position. Both positions are opposed in the sense that the first emphasizes that innate ideas are endowed with perfection, so that the imperfect minds of people could not have created them: God is the origin of these ideas and they are proof of his existence. Thus knowledge is only possible through the intervention of God. For the analysis, both primary and secondary sources were used, emphasizing Descartes' Third and Fifth Meditations, and Kant’s The only possible argument for a demonstration of the existence of God and Critique of Pure Reason to reveal how the latter philosopher redirects the ontological argument by redefining the concept of existence; and by affirming from the logics, in his critical work, that the existence of God cannot be known a priori with analytical propositions.